Forward Time Central Space and Saulyev’s Method for Solving one Dimensional Parabolic Equations with Non Local Condition - Musbah, F. S. (Aljameai, 2022)
Abstract: The purpose of this study is to test and compare two explicit numerical approaches, the conditionally stable forward time central space FTCS and unconditionally stable Saulyev’s method, for solving parabolic equations with a nonlocal boundary condition using different step sizes of time . These methods are based on finite different schemes. All computations are carried out using mathematica wolfram 8.0 software. We have employed these numerical schemes to show the accuracy of their solutions and since they are explicit, their results are compared. The stability of these numerical schemes is also discussed. It should be noted that FTCS method is closer to the exact solution so long as in comparison with Saulyev’s method. On contrary the Saulyev’s method is more stable and gives a good approximation in case . الملخص: الهدف من هذه الدزاسة إختبار ومقارنة طريقتان من الطرق العددية الصريحة وهي طريقة الفروق الأمامية للزمن والمركزية للمسافة FTCS والتي تكون مستقرة بشروط وطريقة ساولوفي والتي تكون مستقرة بدون شروط لحل المعادلات الجزئية المكافئة مع الشرط الغير محلي باستعمال أحجام مختلفة من الخطوات للزمن t. هذه الطرق مبنية على طريقة الفروق المنتهية. كل العمليات الحسابية تم تنفيذها باستخدام برنامج الماتيماتيكا وولفرام 8.0. تم دراسة هذا النوع من الطرق العددية لمعرفة الدقة في الحلول, ولكونهما طرق صريحة تمت المقارنة بين نتائجهما ومناقشة استقرارهما. من خلال النتائج يمكننا التوصل الى ان طريقة ال FTCS تكون قريبة في نتائجها من الحل النظري بشرط بالمقارنة مع طريقة ساولوفي . في المقابل نجد أن طريقة ساولوفي مستقرة بدون شروط وتعطي نتائج جيدة في حالة .